Pengaruh media sosial terhadap pembentukan perubahan identitas nasional di kalangan remaja - Farhatin, Farhatin (Maliki Interdisciplinary Journal, 2025)
Social media has become an inseparable part of the lives of teenagers in today's digital era. Its presence not only influences the way they interact, but also plays a role in the formation and change of their national identity. This journal aims to analyze how social media influences how teenagers perceive their national identity, both in terms of the formation, maintenance, and change of national identity. Through a qualitative approach with literature study methods and in-depth interviews, this study shows that social media acts as a dynamic space where the ideology of nationalism is formed and transmitted, but also opens up space for challenges to a more global and pluralistic national identity. The results of this study are expected to provide insight into the role of social media in forming an adaptive national identity among teenagers.